A revision of the Afrotropical hover fly genus Afroxanthandrus Kassebeer, 2000 (Diptera, Syrphidae), with the description of two new species and one new synonymy – Corrigendum - John M. Midgley; Georg Goergen; Kurt Jordaens (European Journal of Taxonomy)
The present corrigendum corrects figure numbers that were incorrect in Midgley et al. (2024).